(untitled) (Patan Prospective Journal, 2022)
This research examines the perception of secondary level girl students on abortion and abortion services in the context of Nepal. This study employs primary data obtained from 250 adolescent girl students of community schools and bases on descriptive research design using quantitative method. The result reveals that 90 percent of the girl students possess the information of abortion and abortion services while only 80 percent of them have its legal knowledge. Nearly 87 percent of girl students of community schools show their awareness on safe abortion services while remaining others do not have any information about it. The major factors which cause adolescent girls to perform abortion include health of mother, poverty and undesirability of children. The data also exhibits that 72 percent of the respondents chose doctors as the best service providers followed by health assistants (19.2%) in Nepalese societies. It again shows that the skillful health workers are the choices for those who want to get abortion service. Likewise, majority of the respondents show their belief in government hospitals as safer places for this service. Since it came into legal practice in Nepal, many adolescent girls have been performing abortion practices regardless of using proper knowledge, counselling and professional skills. Observed as a sinful act in our community in the previous years, abortion has been taken as a common practice, today.